1983
DOI: 10.1113/jphysiol.1983.sp014799
|View full text |Cite
|
Sign up to set email alerts
|

Apical membrane permeability and kinetic properties of the sodium pump in rabbit urinary bladder.

Abstract: SUMMARY1. Previous studies have shown that aldosterone stimulates the rate of Na+ transport across the rabbit urinary bladder epithelium by increasing the apical membrane permeability to Na+. Paradoxically, ion-sensitive and conventional micro-electrode measurements demonstrated that intracellular Na+ activity aNa+ was essentially unchanged by aldosterone, i.e. aka+ was constant regardless of the rate of Na+ transport. The present study was designed to resolve this apparent contradiction.2. The effects of elev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(42 citation statements)
references
References 27 publications
3
39
0
Order By: Relevance
“…Although there is considerable evidence for in vitro pharmacologic modification of Na channels, there is also some precedent for in vivo alterations of this transport system (27,28). Along these lines, Leng-Peschlow and Marty (29) have observed that, in a surgically created cecal pouch, pretreatment of the pouch with cecal contents over several days resulted in net absorption of Na and water.…”
Section: Discussionmentioning
confidence: 98%
“…Although there is considerable evidence for in vitro pharmacologic modification of Na channels, there is also some precedent for in vivo alterations of this transport system (27,28). Along these lines, Leng-Peschlow and Marty (29) have observed that, in a surgically created cecal pouch, pretreatment of the pouch with cecal contents over several days resulted in net absorption of Na and water.…”
Section: Discussionmentioning
confidence: 98%
“…Perhaps the best example of functional characterization of a newly discovered protein in the urothelium was the amiloridesensitive sodium channel, which is present in the luminal membrane (41,(43)(44). Employing Ussing chambers and conventional as well as ion-sensitive microelectrodes to measure transepithelial resistance, conductance, short-circuit currents, and intracellular Na ϩ activity, the authors dissected the functional and regulatory signature of an ion channel which was ultimately cloned and shown to be the heteromeric epithelial sodium channel (ENaC) (8).…”
Section: Facs or Magnetically Activated Cell Sorting (Macs)mentioning
confidence: 99%
“…A primary action of the hormone is the increase in Na permeability of the apical membrane of these cells, leading to increased Na reabsorption. This has been demonstrated both with electrical measurements on intact epithelia (Nagel and Crabb6, 1980;Palmer, Li, Lindemann, and Edelman, 1982;Lewis and Wills, 1983;Sansom and O'Neil, 1985) and with Na fluxes into isolated membrane vesicles (Asher and Garty, 1988). There is, however, relatively little known about the action of aldosterone at the single channel level.…”
Section: Introductionmentioning
confidence: 95%